Japanalia : - Bush, Lewis (The Japan Times, 1967)
This book consists of thw following many parts: the Japanese zodiac, festivals, gods, demons and goblins, summer spine chilling, the honourable monkey, scarecrows, bookplates, old highways, ships and early maritine trade, kisery and smoking...